54 CEACAM1 in Brain Development and Preterm Brain Injury. (October 2012) - Prager, S; Singer, BB; Keller, M; Bendix, I; Schlager, GW; Herrmann, R; Ergün, S; Felderhoff-Müser, U
Abstract : Background and aims: About 10% of all neonates are born preterm before 37 weeks of gestation. These babies are at high risk to develop morbidities such as neurocognitive disorders (encephalopathy of prematurity) which are a huge burden on the children and their families. Multiple factors are causal, e.g. hyperoxia and maternal/neonatal inflammation. We demonstrated that CEACAM1, a member of the carcinoembryonic antigen-related cell adhesion molecule (CEACAM) family, is expressed ontogenetically in oligodendrocytes of the developing brain. Since CEACAM1 is involved in inflammation-associated signaling we hypothesize that CEACAM1 might contribute to inflammation-induced preterm brain injury. Material and Methods: In a rat model of inflammation-induced encephalopathy of prematurity (LPS at p3), changes in CEACAM1 expression were quantified on RNA level at p6 and p11. Animals were anesthetized, transcardially perfused, and forebrains were immediately removed and snap-frozen. RNA from forebrains was isolated according to standard protocols. CEACAM1 isoform expression was quantified by qRT-PCR. Results: LPS exposure at p3 induces significant changes in CEACAM1 expression in the developing brain. We report a significant increase of the soluble isoform CEACAM1–4C2 at p6, and a subsequent increase of the CEACAM1–4L isoform and an isoform shift from CEACAM1–4S towards CEACAM1–4L at p11. Conclusions: Although underlying mechanisms are still elusive we demonstrate that CEACAM1 expression in oligodendrocytes is significantly altered in a model of inflammation-induced encephalopathy of prematurity. This finding emphasizes our hypothesis that CEACAM1 is involved in detrimental processes in the immature brain.